2019
DOI: 10.1002/term.2866
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and N‐glycoproteomics analysis of an extracellular matrix‐based scaffold‐human treated dentin matrix

Abstract: Extracellular matrix (ECM)-based biomaterials developed from mammalian tissues have been successfully used in preclinical and clinical tissue engineering applications.We have previously reported about the applicability of dentin-based scaffold, treated dentin matrix (TDM), for tooth root regeneration. However, TDM protein composition has not been characterized. Here, we used a shotgun proteomic strategy to profile human TDM proteome. N-glycoproteins were enriched by lectin affinity chromatography and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Similarly, the transcription factor SP1 could regulate KLF4 through a binding site lying in a CpG island in the promoter region of Klf4 [74]. The dentin matrix may be another promising natural biomaterial with which to regenerate the pulpodentinal complex due to its nonimmunogenicity and richness in dentinogenesis-related growth factors [87]. Some possible application forms have been proposed, such as nanostructure demineralised dentin matrix (DDM) treated with different demineralised agents, extracted dentin matrix components, and treated dentin matrix paste (TDMP) [88][89][90][91].…”
Section: Natural and Naturally Derived Substancesmentioning
confidence: 99%
“…Similarly, the transcription factor SP1 could regulate KLF4 through a binding site lying in a CpG island in the promoter region of Klf4 [74]. The dentin matrix may be another promising natural biomaterial with which to regenerate the pulpodentinal complex due to its nonimmunogenicity and richness in dentinogenesis-related growth factors [87]. Some possible application forms have been proposed, such as nanostructure demineralised dentin matrix (DDM) treated with different demineralised agents, extracted dentin matrix components, and treated dentin matrix paste (TDMP) [88][89][90][91].…”
Section: Natural and Naturally Derived Substancesmentioning
confidence: 99%
“…The current research results show that the 3D culture system constructed in this study can solve the problems of cell adhesion density and tightness, and promote cell proliferation and differentiation. For one thing, the protein composition of TDM contains cell adhesion-related proteins, such as fibronectin 1, vitronectin, and laminin, to ensure the tight adhesion of cells attached to its surface [ 8 ]. Ultra-low adhesion dishes allow more cells to grow on the surface of pTDM rather than traditional dishes, resulting in most cells adhering to the bottom of the dishes.…”
Section: Discussionmentioning
confidence: 99%
“…Treated dentin matrix (TDM) from natural tooth tissue has been used as a biological scaffold for bioengineering tooth organs owing to its biological property of providing an odontogenic microenvironment [ 8 , 9 ]. Several studies report the advantages of dental-derived stem cells combined with TDM in bio-root regeneration [ 10 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also contains bone morphogenetic proteins (BMPs) [ 39 ]. The results of a shotgun proteomic strategy applied to profile human TDM proteome showed that collagens, proteoglycans, small integrin-binding ligand N-linked glycoproteins and growth factors were identified [ 40 ], which supplements the evidence showing that a TDM contains a similar protein composition to a native dentin matrix.…”
Section: The Vital Properties Of a Tdmmentioning
confidence: 95%